Flow/acoustics mechanisms in two- and three-dimensional wake vortices - Li, Wenhua (Kansas State University, 2007)
In this study, a vortex particle method is used to simulate incompressible vortical flows, specifically aircraft wake vortices. This is particularly suitable for a wake vortex system that is slowly varying in the axial direction and has a high Reynolds number and low Mach number. The flow field, in the form of vorticity, is employed as the source in the far-field acoustic calculation using a vortex sound formula that enables computation of acoustic signals radiated from an approximated incompressible flow field. In a two-dimensional vortex system, the stretching effect in the axial direction is neglected. The purpose of this study is to focus on vortex core behaviors. A numerical simulation is performed in a more realistic wake consisting of a counter-rotating vortex pair with inviscid ground effects and shear flows. A Kirchhoff spinning-core vortex model is thus used as a starting point. In a vortex system with multiple vortices, such as a complicated aircraft vortex wake vortices, the sound emission frequency of the unsteady vortex core is subjected to change because of interactions between multiple vortices. The behaviors of the influence, indicated by the ratio between the core size and the distance of the vortices, are investigated as well as the underlining vortex core dynamic mechanisms. Cases of co-rotating vortices and a multiple-vortex system composed of two counter-rotating vortex pairs are studied for applications to aircraft wake vortex sound. In three-dimensional vortices, sinusoidal instabilities, which occur in the axial direction at various length scales, result in significant flow structure changes in these vortices, and thus influence their radiated acoustic signals. Cases of vortex rings and a pair of counter-rotating vortices are studied when they are undergoing both long-wave and short-wave instabilities. Both inviscid and viscous interactions are considered and the effects of turbulence are simulated using sub-grid-scale models. A higher peak frequency than the Kirchhoff frequency appears due to the straining field caused by mutual perturbation, under both long-wave and short-wave instabilities. Vortices with the initial core vorticity of the Gaussian distribution and the elliptic distribution are also studied.
Keywords: wake vortex; vortex particle method; acoustics; three dimensional flow; sound; vortex ring; Engineering, Aerospace (0538); Engineering, Mechanical (0548)